Overview of syphilis in a northern Brazilian city from 2013 to 2017 - NONATO, OSVALDO CAMPOS DOS SANTOS; Barbosa Martins, Raissa; Bezerra da Silva Sussuarana, Suzana; Albuquerque da Costa, Layra Lucy Maria (Revista de Epidemiologia e Controle de Infecção, 2020)
Justifications and Objectives: Syphilis is the most widespread bacterial infection in the human population, being the main form of transmission through sexual contact. It was analyzed the epidemiological data of the population of the city of Rio Branco, Acre, Brazil, with a positive diagnosis of syphilis between 2013 and 2017. Methods: This is a descriptive, cross-sectional study, with a quantitative approach applied to data from Acre’s Central Public Health Laboratory of the population infected with T. pallidum. Results: Of a total of 5,239 people infected with syphilis, 56.8% are female between the ages of 20 and 30 years old and self-declared to have mixed ethnicity. Moreover, 1,006 pregnant women, 43% of whom were between 11 and 20 years old and 37.5% were in the 2 nd trimester of pregnancy. For live births, 107 children with early congenital syphilis were diagnosed. Conclusions: Infection prevention information should be intensified, especially for people who are unaware of STIs in the city, such as adolescents, elderly people and indigenous populations, in order to avoid syphilis transmission.